Effects of a health promotion and fall prevention program in elderly individuals participating in interaction groups - Lays Cavallero Pagliosa; Alexandra Renosto
Introduction Falls in elderly people are an increasing public health problem resulting in high costs to health services. Thus, it is essential to invest in the development of actions and programs focused on decreasing such risks. Objective To verify the effects of a program of health promotion and prevention of falls in relation to balance and functional abilities in elderly people participating in interaction groups in Caxias do Sul City, RS State. Materials and methods For this purpose, 14 elderly people were selected for assessment and reassessment through the following instruments: the Barthel Index, Timed Up and Go Test (TUG), Berg Balance Scale (BBS), and a questionnaire to characterize the sample. Over the course of 2 months, group activities were conducted in a multi-sensory and proprioceptive circuit with a frequency of 2 times per week, totaling 14 meetings. Results The average age of participants was about 72 years old, mostly women (78.6%); 64.3% of them had experienced falls, and 92.9% had already practiced physical activities. After the intervention, there was an average increase of 9.14 points in the BBS (p = 0.000) and an average reduction of 4.4 seconds in gait speed on the TUG test (p = 0.000). Conclusion The application of the proposed program resulted in increasing balance and gait performance of the elderly, reducing the risk of falls.